Lifestyle factors associated with pre-metabolic syndrome in young adults: A cross-sectional study of annual health examinations in university students - Haruka Arimori; Akie Moriuchi; Masakazu Kobayashi; Shimpei Morimoto; Seiko Nakamichi; Atsushi Kawakami; Norio Abiru (PLoS ONE, 2026)
The recent global rise in obesity and metabolic syndrome (MetS) among young adults has become a public health concern. Moreover, lifestyle changes were widely reported as a result of preventive measures against the novel coronavirus disease 2019. We conducted a cross-sectional study to investigate lifestyle factors associated with a pre-disease condition prior to MetS in young adults during/post-pandemic era. A survey was distributed to fourth-year students at Nagasaki University in 2023, and medical examination data were collected. Participants who met both high intra-abdominal fat area (IAFA >71.1 cm²) and at least one of the Japanese diagnostic criteria for MetS were categorized as having pre-MetS. The pre-MetS group was compared with the control (non–pre-MetS) group to examine its characteristics using Fisher’s exact test and binomial logistic regression. A total of 856 students participated in this study; of them, 43 (5.0%) were classified as the pre-MetS group. Fisher’s exact test identified significant associations between pre-MetS and breakfast frequency of 2–3 times/week, dining out ≥4 times/week, no or infrequent part-time job, late bedtime, and longer gaming time. Multivariable logistic regression revealed that after mutual adjustment, pre-MetS remained associated with no or infrequent part-time job and longer gaming time. After further adjustment for age, sex, and body mass index, only no or infrequent part-time job and gaming time of ≥4 h/day were significantly associated with pre-MetS. These factors were associated with pre-MetS and might reflect early metabolic alterations; further prospective studies are needed in this regard.